The Covid-19 crisis, Italy and Ms Merkel's turnaround: Will the EU ever be the same again? - Luigi Bonatti; Andrea Fracasso (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The European debt crisis has brought about permanent changes in the Eurozone (EZ). The no-bailout rule was - de facto - removed, new institutions such as the ESM and the banking union were designed and partially implemented, new monitoring and surveillance schemes, such as the macroeconomic imbalance procedure, were introduced. In this way, the functioning of the EZ has been irreversibly transformed. Now, as a consequence of the Covid-19 pandemic, a new - even more devastating - crisis has hit the EU. In response to this crisis, it is taking place a substantive - if not also formal - infringement of well-established principles such as those preventing the ECB from monetizing government deficits and the EU from acting as a transfer union with a common debt. The latter development was made possible by German Chancellor Angela Merkel's abandonment of her reiterated opposition to substantial intercountry transfers and any form of debt mutualization. This turnaround was motivated by the exceptional circumstances due to the pandemic and was presented by the German Chancellor as a one-off policy change. The risk that Italy's fragile financial, economic and political situation, exacerbated by the current crisis, could destabilize the entire EZ in the absence of sizeable external assistance was probably one of the main determinants of the German government's policy shift. We argue that, although this shift is sufficient to prevent Italy from plunging into a major financial and political crisis in the short term, thus buying time, it is far from sure that it will be sufficient to drive Italy into a sustainable and satisfactory growth path, so as to avoid that in the longer term it will be in need of further financial support from EU institutions and member states. Hence, the latter may again face the dilemma of whether to provide financial assistance to the EZ most vulnerable countries, thus making permanent what was supposed to be temporary, or exposing the EZ to a possible implosion.
Keywords: 330; Schuldenkrise; Coronavirus; Coping-Strategie; Deutschland; Italien; Europäische Integration